Spline Computation for Solving Magnetohidrodynamics Free Convection Flow (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper, we construct numerical algorithms for solving Magnetohidrodynamics(MHD) free convection flow rate whichhas been discussed in detail. It is observed that, for a nonlinear system of differential equation, the spline model of ninedegree is used, effectiveness and accuracy of this new method are presented. Several theorems relating the order of theninth spline to the saturation of the estimator are proved. Some results of consistency are given and an applicationMHD system is given.